Development of a small island water information network - Malomo S. (Commonwealth Science Council LondonGB, 1999)
Provides information on the Small Island Water Information Network (SIWIN) which is now active in four small island regions of the world viz.: the Caribbean, Indian Ocean, Mediterranean and the South Pacific.